Heart failure outcomes according to heart rate and effects of empagliflozin in patients of the EMPEROR-Preserved trial - Böhm, Michael; Butler, Javed; Mahfoud, Felix; Filippatos, Gerasimos; Ferreira, João Pedro; Pocock, Stuart J.; Slawik, Jonathan; Brückmann, Martina; Linetzky, Bruno; Schüler, Elke; Wanner, Christoph; Zannad, Faiez; et al. (European journal of heart failure, 2022)
Aims Empagliflozin reduces cardiovascular death (CVD) or heart failure hospitalization (HHF) in patients with heart failure and preserved ejection fraction (HFpEF). Treatment effects and safety in relation to resting heart rate (RHR) have not been studied. Methods and results The interplay of RHR and empagliflozin effects in EMPEROR-Preserved was evaluated. We grouped patients (n = 5988) according to their baseline RHR (<70 bpm [n = 2650], 70-75 bpm [n = 967], >75 bpm [n = 1736]) and explored the influence of RHR on CVD or HHF (primary outcome) and its components in sinus rhythm or atrial fibrillation/flutter (AF) and adverse events. We studied the efficacy of empagliflozin across the RHR spectrum. Compared to placebo, empagliflozin did not change heart rate over time. The primary outcome (p for trend = 0.0004) and its components CVD (p trend = 0.0002), first HHF (p for trend = 0.0099) and all-cause death (p < 0.0001) increased with RHR only in sinus rhythm but not AF. The risk increase with RHR was similar in patients with heart failure and mildly reduced ejection fraction (left ventricular ejection fraction [LVEF] 40-49%) and HFpEF (LVEF ≥50%). Baseline RHR had no influence on the effect of empagliflozin on the primary outcomes (p for trend = 0.20), first HHF (p for trend = 0.49). There were no clinically relevant differences in adverse events between empagliflozin and placebo across the RHR groups. Conclusion Resting heart rate associates with outcomes only in sinus rhythm but not in AF. Empagliflozin reduced outcomes over the entire RHR spectrum without increase of adverse events.